2012
DOI: 10.1002/gcc.21940
|View full text |Cite
|
Sign up to set email alerts
|

Segmental chromosome aberrations converge on overexpression of mitotic spindle regulatory genes in high‐risk neuroblastoma

Abstract: Integration of genome-wide profiles of DNA copy number alterations (CNAs) and gene expression variations (GEVs) could provide combined power to the identification of driver genes and gene networks in tumors. Here we merge matched genome and transcriptome microarray analyses from neuroblastoma samples to derive correlation patterns of CNAs and GEVs, irrespective of their genomic location. Neuroblastoma correlation patterns are strongly asymmetrical, being on average 10 CNAs linked to 1 GEV, and show the widespr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…These data suggest that, although altering mitotic progression, TPX2 overexpression per se is not inducing a high percentage of chromosomal unbalanced daughter cells. Indeed, tumour-associated signatures, including TPX2 up-regulation, display overexpression of other cell cycle or mitotic regulators [24,28,29], and particularly of Aurora-A [25], suggesting that co-deregulation of other factors may underlie chromosomal instability in TPX2-overexpressing cells. In addition, TPX2 may have a role in the maintenance, rather than the establishment, of chromosomal instability in cancer cells, by fuelling mitotic errors through impairing correct spindle assembly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that, although altering mitotic progression, TPX2 overexpression per se is not inducing a high percentage of chromosomal unbalanced daughter cells. Indeed, tumour-associated signatures, including TPX2 up-regulation, display overexpression of other cell cycle or mitotic regulators [24,28,29], and particularly of Aurora-A [25], suggesting that co-deregulation of other factors may underlie chromosomal instability in TPX2-overexpressing cells. In addition, TPX2 may have a role in the maintenance, rather than the establishment, of chromosomal instability in cancer cells, by fuelling mitotic errors through impairing correct spindle assembly.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments in human tumour cells showed that TPX2 overexpression also affects spindle assembly [21,24]. Several tumours overexpress TPX2 [2,[25][26][27], often within signatures of mitotic genes, frequently including Aurora-A [25,28,29]. Therefore, cancer cell lines may already display deregulated levels of mitotic factors [30] and the actual effect of increased TPX2 levels on an unperturbed mitosis would be more precisely addressed using non-cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…We also showed that this behavior is not restricted to dosage effects induced by segmental alterations and could therefore involve a larger fraction of genes. Genomic instability indirectly affects the expression of many more genes than those located in CNAs, both in neuroblastoma 44 and other tumors 45 , thus altering the levels of mRNAs in normally biallelic loci. These altered levels could also be “corrected” by changes in translational efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The median survival of patients correlated with TPX2 levels, with high TPX2 being associated with overall poor survival (Li et al, 2010). TPX2 was also identified among 9 genes which are significantly overexpressed in grade III vs grade I meningiomas (Stuart et al, 2011) and among 14 genes with elevated expression in high-risk neuroblastomas with 1p loss and MYCN amplification (Ooi et al, 2012).…”
Section: Prognosismentioning
confidence: 97%